Association between Social Support and Three Types of Loneliness among Rural Older Adults in Johor, Malaysia - Hussein, Siti Zuhaida; Khalip, Norazilah; Ismail, Selamah; Hatta, Mohammad Fariq (UI Scholars Hub, 2022)
Background: Social support plays a vital role in ensuring the well-being and quality of life of older people. Methods: This cross-sectional survey was conducted among 380 older adults residing in a rural district in Johor, Malaysia. A proportional stratified random sampling was used to examine the relationship between social support and three types of loneliness. The data were collected using the Short-Form Social and Emotional Loneliness Scale for Adults and Lubben Social Network Scale–6, with p < 0.05 considered as statistically significant. Data analysis was performed using the Statistical Package for the Social Sciences Statistics 26.0 for Windows. Results: More than half of the older adults in this rural area received social support from their family and friends. The results showed a significant relationship between family support and social (p < 0.01), emotional (p < 0.001), and family loneliness (p < 0.01). Multiple logistic regression analysis revealed that social support from friends (p < 0.001) and family (p = 0.02) predicted significantly social loneliness. Family support is a significant predictor of emotional loneliness (p = 0.001), and friend support is a significant predictor of family loneliness (p = 0.001). Conclusions: The support from family members and friends is recommended to combat loneliness in older adults.